(untitled) (Mustansiria Dental Journal, 2018)
Aim: The aim of this in vitro study was to compare the effect of immediate versus delayed dowel space preparation using two techniques (peeso reamers and hot pluggers) on the apical seal of Resilon/ Epiphany obturation system. Methodology: Fifty freshly extracted human teeth with single and straight canals were used in this study. The roots were instrumented using the step-back technique, K-files with circumferential filing action and copious irrigation of 2.5% sodium hypochlorite and 17% solution of aqueous EDTA to remove smear layer. The canal obturation of all roots was performed with lateral condensation technique using Resilon/Epiphany Obturation system. Then the obturated roots were randomly distributed into 5 experimental groups (10 teeth for each group); one control group, and 4 experimental groups according to the technique of dowel space preparation (peeso reamers and hot pluggers) either immediately after obturation or after one week later. After this period, the external surfaces of all roots were coated by two layers of sticky wax except for the apical 2 mm and were submerged in 2% methylene blue dye for 3 days at 37ºC. Then all roots were longitudinally sectioned for linear measurement of dye penetration through the apical foramen using a stereomicroscope. The data obtained were analyzed statistically using ANOVA and Student t-tests. Results: Significantly more apical leakage (P<0.05) in groups that received delayed dowel space preparation using either peeso reamers or hot pluggers compared with control group and no significant differences (P>0.05) between immediate and delayed dowel space preparation using either technique. Conclusion: Resilon/ Epiphany obturation system can received immediate and delayed preparation using conventional methods of dowel space preparation, however immediate preparation was preferred according to the results of this experiment.